An Arts‐Based Approach to Conceptual Educational Practice - Nickerson‐Crowe, Kate (Canadian Journal of Education/Revue canadienne de l'éducation, 2005)
I present autobiographical writing and photographic imaging, an arts‐based research methodology, to understand my personal knowledge as a means to understand my professional knowledge. Using my passions for writing and photography, I explore the conflicts, opportunities, and purposes of using a visual form of arts‐based narrative inquiry from a postmodern perspective. I demonstrate that the relationship between arts‐based narrative inquiry and educator/researcher reflexivity and transformation allows educators to focus their passions towards a greater understanding of what it means to teach. Keywords: arts‐based research; narrative research; personal, professional knowledge development L’auteure présente une méthode de recherche axée sur les arts, laquelle fait appel à des écrits autobiographiques et à des photographies, autant de façons pour elle de pencher sur ses connaissances personnelles afin de comprendre ses connaissances professionnelles. Passionnée d’écriture et de photographie, l’auteure explore les conflits, les occasions et les buts liés à l’utilisation d’une forme visuelle de recherche narrative dans une perspective postmoderne. Elle démontre comment la relation entre la recherche narrative, la réflexion et la transformation de l’enseignant/chercheur permet aux éducateurs d’orienter leurs passions vers une meilleure compréhension du sens à donner à l’enseignement. Mots clés : recherche axée sur les arts, recherche narrative, approfondissement des connaissances personnelles et professionnelles.